Moment frames – concentrically braced frames dual systems: analysis of different design criteria. Issue 1 (2nd January 2016) - Longo, Alessandra; Montuori, Rosario; Piluso, Vincenzo
Abstract : In this paper, a design methodology based on the theory of plastic mechanism control (TPMC) is presented for dual systems combined by moment resisting frames and concentrically braced frames (MRF–CBF dual systems). The study is focused on the design of structures failing in global mode, i.e. whose collapse mechanism is characterised by the yielding of all the tensile diagonals, the buckling of the compressed ones, and the development of plastic hinges at all the beam ends and at the base of first-storey columns. The results of push-over analyses and nonlinear dynamic analyses carried out with reference to MRF–CBF dual systems designed according to the proposed procedure are compared with those obtained with reference to the same structural scheme designed according to Eurocode 8. The advantages obtained in terms of seismic performances are outlined and also economic issues are investigated pointing out the convenience of seismic design based on TPMC.